ENHANCING COMMUNICATION COMPETENCE VIA ASSESSMENT ACTIVITIES OF SPEAKING SKILLS FROM COMMUNICATIVE APPROACH - Dao, Tam Thi; Thu, Nguyen Thi Hong (LLT Journal: A Journal on Language and Language Teaching, 2020)
In teaching language, testing and evaluation play a very important role in helping teachers identify the proficiency, levels of acquiring knowledge, language skills of students, and assessing the problems that exist in learning and teaching. Thanks to assessment activities, teachers actively adjust and improve teaching methods, helping students solve the difficulties they face. This article focuses on the assessment activities of English-speaking skills through Communicative Approach (CA) for law-major students in order to improve speaking skills effectively. The study was conducted to 80 law-major students at the Hanoi Law University. The findings showed that communicative approach assessment measures bring about a number of benefits and challenges as well as expresses the perspectives of students towards applying CA in assessing speaking skill.